Справочник по полупроводниковым диодам, транзисторам и интегральным схемам - Горюнов Н. Н. Николай Николаевич; Клейман А. Ю. Аркадий Юрьевич; Комков Н. Н. Николай Никитович; Толкачева Я. А. Янина Алексеевна; Терехин Н. Ф. Николай Федорович (Москва, Энергия, 1979)
Авт. указаны на обороте тит. л.